Enhancing financial stability in Islamic banks: An investigation of determinants during the COVID-19 in Indonesia - Ardita Herniati Putri; Zulpawati Zulpawati; Imronjana Syapriatama; Riduan Mas'ud; Muhammad Muhajir Aminy; Mohamed Saleem Ahamed Riyad Rooly (Journal of Enterprise and Development (JED), 2024)
Purpose — This study investigates the determinants of Islamic banks' stability in Indonesia amidst the Covid-19 pandemic.Method — Employing a causality-associative quantitative approach, the research utilizes purposive sampling and secondary data collection from monthly financial reports on the official websites of OJK (Financial Services Authority) and BI (Bank Indonesia). Statistical techniques including normality test, multicollinearity test, t-test, f-test, R2 test, and multiple linear regression, aided by SPSS version 22 and Microsoft Excel, are employed for data analysis.Result — The results reveal that Islamic banks' total assets significantly positively influence their stability in Indonesia. Additionally, variables such as Operational Costs to Operational Income (OCOI) ratio and BI 7-Day Reverse Repo Rate (BI7DRR) exhibit significant negative effects on Islamic banks' stability. Practical implications — Understanding the influence of total assets, Operational Costs to Operational Income (OCOI) ratio, and the BI 7-Day Reverse Repo Rate (BI7DRR) on Islamic banks' stability in Indonesia during the Covid-19 pandemic can guide policymakers and bank management in implementing measures to strengthen resilience and mitigate risks, such as strategic asset management and cost optimization strategies.